Effects of farmers' social networks on knowledge acquisition: Lessons from agricultural training in rural Indonesia - Ayu Pratiwi; Aya Suzuki (Journal of Economic Structures, 2017)
Agricultural information is transferred through social interactions; therefore, ties to agricultural informants and network structures within farmers' local neighborhoods determine their information-gathering abilities. This paper uses a spatial autoregressive model that takes account of spatial autocorrelation to examine such network connections, including friendship networks and advice networks, upon farmers' knowledge-gathering abilities during formal agricultural training. We found that peer advice networks are important to support knowledge-gathering activities, while friendship networks are not. Further examination of network structures confirms that farmers who occupy a central position in their local neighborhood networks are found to perform better in learning outcomes to some extent, indicating that local network position is positively related to problem-solving ability in an unknown environment outside their locale.
Keywords: 330; Informationsverhalten; Landwirte; Soziales Netzwerk; Räumliche Statistik; Indonesien